(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Indian populationcomprises approximately one sixth of the world’s population. Among this, tenpercent of the population possesses a large proportion of the total wealth ofindia. Interestingly, during the past few years, Indian has demonstrated awelcome willingness to innovate and to think afresh about financial services toalleviate poverty. The poverty, reduction has become the object ofunprecedented attention at national and international level. The dynamic growthof the microfinance industry has been promoted not only by market forces butalso by conscious actions of national governments, Non-government organizationand the donors who view microfinance as an effective tool for eradicatingpoverty. Thus the concept of micro finance gained growing recognition as aneffective tool in improving the quality of life and living standards of poorpeople. This paper argues that microfinance can be considered an improvementelement for an effective poverty reduction strategy. It shows that access andefficient provision of microcredit can enable the poor to smooth theirconsumption, manage their risks better, gradually build their assets, developtheir micro enterprises, enhance their income earning capacity and enjoy animproved quality of life.